2009
DOI: 10.1210/jc.2009-0212
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone-Related Regulation of Gene Expression in Human Fatty Liver

Abstract: These data suggest that impaired thyroid hormone action may contribute to altered patterns of gene expression in fatty liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 36 publications
6
103
0
3
Order By: Relevance
“…Another possibility is that the RTH action might influence hepatic insulin sensitivity. This hypothesis is supported by a recent report suggesting that T3-responsive genes account for most of the dysregulated transcripts in the livers of obese and insulin resistant subjects (Pihlajamäki et al, 2009).…”
Section: Hypothyroidismsupporting
confidence: 63%
“…Another possibility is that the RTH action might influence hepatic insulin sensitivity. This hypothesis is supported by a recent report suggesting that T3-responsive genes account for most of the dysregulated transcripts in the livers of obese and insulin resistant subjects (Pihlajamäki et al, 2009).…”
Section: Hypothyroidismsupporting
confidence: 63%
“…The reason for this effect is not known, but it may result from transcriptional regulation and/or better adaptation to bone marrow niche conditions [15][16][17]. Overall, elevated or normal expression of the components of MRC complex I and II suggests that OXPHOS reaction and electron flow can be properly initiated, but deregulated expression of the members of MRC complex III may "derail" and/or slow down the flow of electrons causing their "leakage".…”
Section: Discussionmentioning
confidence: 99%
“…TRβ mediates the majority of the actions of T3 in the liver (23), playing an important role in regulating metabolism (24,25), regeneration (26), senescence (27), and carcinogenesis (28). Recent findings suggest that nonalcoholic fatty liver disease, which can progress to liver fibrosis, cirrhosis, and hepatocellular carcinoma, is associated with impaired thyroid action in the liver (29)(30)(31)(32). We have shown that expression of TRβ1 in liver cancer cells represses TGF-β-mediated proliferation and induction of metalloproteases (33), suggesting that the receptor could antagonize the response to the growth factor and, therefore, influence carcinogenesis.…”
mentioning
confidence: 99%